THE INTERCONNECTIVITY OF WEATHER SYSTEM AND OZONE CONCENTRATION OVER WEST AFRICA (Journal of Science and Technology, 2016)
The relationship between some meteorological parameters and ozone distributions as revealed by satellite EPTOM over four West African stations namely, Lagos (Nigeria), Dakar (Senegal) Lamto (Ivory Coast) and Ekona (Cameroon) was studied for the period 1997 to 2002. The mean ozone concentration over these stations for the period were 270.8±0.3DU at Lagos, 264.9±0.3DU at Dakar, 269.8±0.3DU and 269.0±03DU at Lamto and Ekona respectively. The average monthly maximum ozone concentration of 288.6DU and 285.1DU respectively were observed for Lagos and Dakar, between July and August, which coincided with the period of tropical summer rain- fall over the West African region. This coincidence could be attributed to reduction in the effect of the extra-tropical suction pump (ETSP) action responsible for the transportation of ozone concentration from the tropical stratosphere into the mid and high latitudinal region. This re- duction may be due to decrease in the atmospheric heat engine expected to drive the ETSP, as the tropical surface temperature and evaporation are at their minimum during the raining sea- son. The surface temperature and evaporation at Lagos-Nigeria both had significant negative correlation values of -0.73 and -0.68 with the ozone concentration respectively.